Assessment of social protection for families with children in the EU member states - Baiba Mistre; Inguna Leibus; Gunita Mazure (Contemporary Economics, 2024)
The extent of social protection provided to families with children varies according to each country's unique economic, social, and demographic conditions. The most important factors for assessing social protection were studied and identified by means of the multivariate statistical analysis method, and the level of social protection was identified through cluster analysis in order to evaluate the level of social protection for families with children in the EU Member States. The research resulted in the classification of factors characterizing social protection for families with children into three groups: demographic, social, and economic. Respectively, the EU Member States may be divided into four different clusters. The most generous social protection for families with children is reported by the countries included into Cluster 4 (Scandinavia and Western Europe - welfare states), which spend a larger proportion of expenses on social protection compared to the other countries. Countries with greater demographic problems and low social protection are included into Cluster 2 (Southern Europe). Ireland, which is the only country in Cluster 1, has the best demographic and economic situation. Relatively weaker economic and social development is demonstrated by the EU Member States belonging to Cluster 3 (Central Europe, Eastern Europe and Portugal); however, the demographic situation indicators in these countries are above the EU average indicator and they do not significantly differ from the indicators of the countries belonging to Cluster 4.
Keywords: I38; I39; 330; social protection; families with children; cluster; EU Member States